Multifunctional CeO2 incorporated Fe2O3 anchored on a rich porous structured carbon backbone for supercapacitors and adsorption of acid orange II. Issue 17 (27th July 2022) - Zhang, Hang; Xia, Lijuan; Tang, Jianping; Li, Yuan; Wang, Lei; Ouyang, Chuying; Zhong, Shengliang
Abstract : Multifunctional porous CeO2 –Fe2 O3 /C for supercapacitor electrode materials and organic dye acid orange II adsorption obtained by hydrothermal and N2 atmosphere pyrolysis of Ce–Fe coordination polymers formed from Ce and 1, 1′-dipentadecadienoic acid. Abstract : Cerium dioxide–hematite/carbon porous microspheres (CeO2 –Fe2 O3 /C, CFC) with a rough surface and a particle size of approximately 1 μm were manufactured through a simple solvothermal and then pyrolytic process using 1, 1′-dipentadecadienoic acid (DDA) as both a ligand and a metal core. Cerium ions are first coordinated with carboxylic acid at room temperature to produce Ce-DDA coordination polymers (CPs) with a rich pore structure, and then calcined in a protective gas atmosphere to produce a carbon skeleton that retains the porous states, while the Ce/Fe ions in the complex remained bonded to oxygen. Due to the massive electron gain/loss valence of cerium ions (Ce 3+ /Ce 4+ ) and the strong conductivity of iron ions, the prepared CFC can indeed perform ion-proton exchange rapidly and moreover show high stability. The CFC has a specific capacitance of 803 F g −1 at a scan rate of 1 mV s −1 for supercapacitor electrode materials. Moreover, it displays an excellent capacitance retention of 95% after 10 000 cycles, indicating that the material has outstanding cycling stability and potential applications in the electrode materials of supercapacitors. Furthermore, CFC has a strong adsorption effect for degrading acid orange II dye (AO7), with a high degradation rate of over 96% after 25 min at various pH (pH = 2, 4, 6, 8, 10, 12), showing that the sample has an excellent adsorption effect throughout a wide pH range. This newly designed CFC has excellent adsorption activity and exceptional supercapacitive cycling stability, making it ideal for wastewater treatment and energy storage applications.